A26 Cognitive and behavioural changes in prodromal and diagnosed hd. (13th September 2016) - Paulsen, Jane S; ,
Abstract : Background: Though the movement disorder characteristic of HD has been a hallmark sign, the importance of cognitive and behavioural aspects of Huntington's disease has become more prominent over the past decade. Aims: (1) To provide an overview of cognitive and behavioural changes in HD; (2) To review brain circuitry believed to contribute to HD changes; (3) To emphasise the importance of cognitive and behavioural changes in diagnosis and clinical trials. Methods: Twelve years of study of the prodrome and eventual diagnosis of HD in 32 sites around the world has revealed a great deal about the onset and progression of HD. Data from Predict-HD will be used to inform the audience on the progression of HD in over 1100 persons with the CAG expansion. Results: Distinct changes are evident in cognition and behaviour over 15 years before a motor diagnosis is given in the clinic. Subsets of at risk individuals can be determined with cognitive, motor, genetic and demographic information. Measures of cognition and behaviour are associated with brain imaging, genetic and levels of work, domestic and emotional capacities. Conclusions: Diagnostic criteria for HD requires revision to include cognitive impairment. Treatment guidelines might benefit from compensatory methods to address cognitive and behavioural changes. Clinical trial outcomes may better reflect the full spectrum of HD processes with consideration of a more comprehensive assessment of HD-related changes.